2015
DOI: 10.4314/mmj.v27i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence and Direct Treatment Cost among Diabetes Patients Attending a Tertiary Healthcare Facility in Ogbomosho, Nigeria

Abstract: BackgroundDiabetes mellitus (DM) is now prevalent in many countries in subSaharan Africa, with associated health and socioeconomic consequences. Adherence to antidiabetic medications has been shown to improve glycaemic control, which subsequently improves both the short-and longterm prognosis of the disease. The main objective of this study was to assess the level of adherence to antidiabetic drugs among outpatients in a teaching hospital in southwestern Nigeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 43 publications
6
39
3
Order By: Relevance
“…The relationship between medication cost and adherence is well established, and there is a wide variation in adherence to diabetic medication worldwide, with reported non-adherence rates of approximately 40% in India and 50% in Malaysia [91]. This issue is also important in countries such as Nigeria and India, where the majority of patients pay 'out of pocket'.…”
Section: Affordability and Accessibility Of Type 2 Diabetes Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between medication cost and adherence is well established, and there is a wide variation in adherence to diabetic medication worldwide, with reported non-adherence rates of approximately 40% in India and 50% in Malaysia [91]. This issue is also important in countries such as Nigeria and India, where the majority of patients pay 'out of pocket'.…”
Section: Affordability and Accessibility Of Type 2 Diabetes Treatmentmentioning
confidence: 99%
“…In a study of patients with type 2 diabetes attending a tertiary hospital clinic in Nigeria, oral antihyperglycaemic agents (metformin alone or in combination) were the most prescribed drugs. According to study participants, common factors that may affect adherence to medications included cost of treatment (20.2%) and nonavailability of prescribed medications (10%) [91]. Even in higher-income countries, patients may be deterred from initiating essential medications because of cost, undermining adherence and risk factor control, as reported in an observational, new-prescription cohort study that evaluated the effect of out-of-pocket cost on medication initiation and adherence in patients with diabetes in California, USA [92].…”
Section: Affordability and Accessibility Of Type 2 Diabetes Treatmentmentioning
confidence: 99%
“…Worldwide studies using various research assessment instruments and systematic reviews have addressed issues of poor medication adherence among diabetes patients. [17][18][19][20][21][22]37 In this study, medication adherence was assessed using MMAS-8. It is a reliable and validated scale.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Worldwide, studies on medication adherence among diabetic patients have shown a wide variation. [17][18][19][20][21][22][23][24] In India, [25][26][27] Limited studies from Southern and Northern regions of India have documented wide variation in the medication adherence and have addressed the issues of nonadherence in diabetic patients. 21,[28][29][30][31][32][33] AIM Therefore, this study was conducted to assess the medication adherence among type II diabetic patients attending a tertiary care hospital in Navi Mumbai, India.…”
Section: Introductionmentioning
confidence: 99%
“…For instance in Nigeria, typically household savings and family support are needed to fund treatments for patients with T2DM, with a mean monthly expenditure of US$356 per patient (Okoronkwo et al, 2016) similar to other studies (Mapa-Tassou et al, 2019). In addition, for patients with diabetes in Nigeria, the costs of medicines can account for over 70% of total direct medical costs (Fadare et al, 2015). Greater use of generic medicines could help reduce these costs (Akunne et al, 2016); however, there are issues with the quality of generics in Nigeria which needs to be addressed (Fadare et al, 2016).…”
mentioning
confidence: 92%